Synthesis of carboxymethyl cellulose lithium by weak acid treatment and its application in high energy-density graphite anode for Li-ion batteries - Park, Hyunjung (2020)
Carboxymethyl cellulose lithium (CMC-Li) has recently been explored as a promising binder for Li-ion batteries because of enhanced Li+ ion flux. CMC-Li has been generally prepared by CMC acid form (CMC-H) as an intermediate product treated with a strong acid, which considerably causes a polymer degradation. Here, we report a synthesis method of CMC-Li through the use of a weak acid (acetic acid) and its application in a high energy-density graphite anode. CMC-Li synthesized by acetic acid (CMC-Li (A)) exhibits enhanced physicochemical properties including an appropriate viscosity of ∼3000 mPa·s at a shear rate of 10 s-1, good slurry stability, and strong adhesion force of 1.4 gf/mm compared to those of CMC-Li synthesized by hydrochloric acid. The high energy-density graphite anode prepared with CMC-Li (A) shows higher charge/discharge capacities and capacity retentions in various rates of 0.05-2 C than those of the electrode prepared with CMC-Na that might be due to the enhanced Li+ ion flux upon cycling.